Endometriosis at Caesarian Section Scar - Gandapur, Abdus Salam Khan; Inayat, Kausar; Riaz, Mariam; Nadeem, Seema (International Journal of Pathology, 2018)
Endometriosis is the presence of endometrial glands and stroma in sites other than the uterus. It is an importantcause of morbidity in women. It is common gynecological problem and is sometimes presented to the generalsurgeons as lump in the abdomen. It should be included in the differential diagnosis of lumps in the abdomen infemales. We report a case of abdominal wall endometriosis following a succeeding three caesarian sections. Thepatient presented with complaints of swelling, severe pain in the abdomen for the last 3 months. The diagnosiswas conformed by Biopsy.